Evaluation of antibacterial activity from phytosynthesized silver nanoparticles against medical devices infected with Staphylococcus spp. Issue 1 (February 2017) - Jyoti, Kumari; Singh, Ajeet
الملخص: أهداف البحث: تُعتبر التكونات الحيوية الرقيقة والعدوى البكتيرية على سطح المعدات الطبية مثل الأطراف الاصطناعية وأنابيب القشطرة تحد خطير لعلم الطب الحيوي. فشلت أغلب الطرق التقليدية مثل العلاج بالمضادات الحيوية واستبدال المعدات الطبية بسبب ضعف فاعليتهم في البيئة الطبية. استهدفنا في هذه الدراسة منع الإصابة بالعدوى ببكتيريا ستافيلوكوكس إبيديرميدس (٣٥٩٨٤) وبكتيريا ستافيلوكوكس أوريوس (٧٤٠) المسببتين للأمراض والمعروفتين بأنهما سلالتان تشاركان في إصابات بشرية ومقاومتان للعلاج بالمضادات الحيوية٬ وذلك باستخدام طلاء الجسيمات النانونية الفضية المصنعة نباتيا. طرق البحث: تم تصنيع الجسيمات النانونية الفضية باستخدام المستخلص المائي لأوراق بيربرس أيشياتيكا، وتم تمييزها باستخدام جهاز التحليل الطيفي فوق البنفسجي، وجهاز حيود الأشعة السينية، وجهاز "فورييه" لتحويل طيف الأشعة تحت الحمراء، والمجهر الإلكتروني المسحي، ومجهر القوة الذرّية، والتحليل الطيفي المبني على تشتت الطاقة، والمجهر الإلكتروني الانتقالي وحيود الإلكترون لمنطقة محددة. وقد تم عد خلايا البكتيريا الحية باستخدام عداد المستعمرات الرقمي. النتائج: أظهرت النتائج بأن الجسيمات النانونية الفضية كانت في النطاق الحجمي ١٥-٣٥ نانومتر، وكانت متبلورة على شكل بنية مكعبة مركزية الوجوه. إضافة إلى ذلك فإن طلاء الجسيمات النانونية الفضية على الأسطح الزجاجية تسبب في نشاط فاعل قاتل للبكتيريا. الاستنتاجات: تشير هذه الدراسة إلى أن الجسيمات النانونية الفضية المصنعة نباتيا والمتوجة بجزيئات حيوية مختلفة موجودة في مستخلص أوراق بيربرس أيشياتيكا المطلية على سطح زجاجي تساعد على منع عدوى المعدات الطبية ببكتيريا ستافيلوكوكس إبيديرميدس وبكتيريا ستافيلوكوكس أوريوس. وبذلك فإن طلاء الأسطح الزجاجية بالجسيمات النانونية الفضية المصنعة نباتيا قد يوفر عاملا فاعلا مضادا للبكتيريا في علاج عدوى الجهاز الطبي. Abstract: Objectives: Biofilm formation on the surface of medical devices, such as artificial prosthetics and catheters, are serious challenges to biomedical science. Most conventional methods, such as antibiotic therapy and medical device replacement, have failed because of low efficiency in medical environments. In the present study, we aimed to prevent infection by human pathogens Staphylococcus epidermidis (35984) and Staphylococcus aureus (740), which are resistant to antibiotic therapy. To prevent these infections, phytosynthesized silver nanoparticles (AgNPs) coating was tested. Methods: The AgNPs were synthesized using aqueous extract of Berberis asiatica leaves and were characterized by UV–vis spectroscopy, X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), atomic force microscopy (AFM), energy dispersive spectroscopy (EDS), transmission electron microscopy (TEM), and selected area electron diffraction (SAED). The viable cells of bacteria were counted using a digital colony counter. Results: AgNPs were 15 nm–35 nm in size and crystallized in a face-centred-cubic structure. Furthermore, the AgNPs coating on glass surfaces were bactericidal. Conclusions: This study suggested that phytosynthesized AgNPs capped with various biomolecules present in leaf extracts of B. asiatica coated on glass surface prevent S. epidermidis and S. aureus associated infections of medical devices. Thus, coating of phytosynthesized AgNPs on glass surfaces may provide efficient antibacterial treatment of infected medical devices.